Psychiatric morbidity in people with autoimmune arthritides as a model of inflammatory mechanisms in mental disorders - Formánek, Tomáš; Mladá, Karolína; Mohr, Pavel; Lim, Mao Fong; Olejárová, Marta; Pavelka, Karel; Winkler, Petr; Osimo, Emanuele Felice; Jones, Peter B; Hušáková, Markéta (BMJ mental health, 2025)
BACKGROUND: Rheumatoid arthritis (RA) and axial spondyloarthritis (axSpA) are autoimmune illnesses characterised by chronic inflammation demonstrating differential associations with psychiatric conditions. OBJECTIVE: In this matched-cohort study, we aimed to investigate whether the associations between these inflammatory illnesses and mental disorders are predominantly the consequence of the burden of the former or whether common causes might underpin the susceptibility to both. METHODS: Using Czech national inpatient care data, we identified individuals with RA or axSpA during the years 1999-2012. We investigated the occurrence of psychiatric outcomes up to 2017 using stratified Cox proportional hazards models. In evidence triangulation, we assessed the potential moderation by age at inflammatory illness, the associations relative to counterparts with other similarly burdensome chronic illnesses and the temporal ordering of conditions. FINDINGS: Both RA and axSpA were associated with mood and anxiety disorders and behavioural syndromes. In evidence triangulation, the associations with depression showed a decreasing age-at-inflammatory-illness gradient in RA; the association between RA and depression was stronger than that between other chronic illnesses and depression; and excluding prevalent depression attenuated the RA-depression association. RA showed consistent inverse associations with schizophrenia and Alzheimer's disease. CONCLUSIONS: Common aetiologies might be involved in increasing the risk of developing both RA and depression. The consistent inverse associations between RA and schizophrenia and between RA and Alzheimer's disease suggest that at least part of these associations might also be a consequence of shared aetiologies as well as potential medication effects. CLINICAL IMPLICATIONS: People with autoimmune arthritides are more likely to experience mood and anxiety disorders, even relative to counterparts with other similarly burdensome chronic illnesses.
Keywords: senioři; Spondylarthritis; Inflammation; Česká republika; Cohort Studies; zánět; Middle Aged; mužské pohlaví; Adult; Czech Republic; kohortové studie; Mental Disorders; ženské pohlaví; Humans; spondylartritida; Arthritis, Rheumatoid; lidé středního věku; revmatoidní artritida; duševní poruchy; dospělí; Female; Aged; lidé; Male